Observations on the Ultrastructure of Antennal Sensilla of Adult Glenea cantor (Cerambycidae: Lamiinae). Issue 2 (19th March 2020) - Dong, Zishu; Yang, Yubin; Dou, Fugen; Zhang, Yujing; Huang, Huixin; Zheng, Xialin; Wang, Xiaoyun; Lu, Wen
Abstract: The external morphology and distribution of antennal sensilla of Glenea cantor Fabricius were studied with scanning electron microscopy. The antennae of G. cantor were observed to be filiform, consisting of scape, pedicel, and flagellum (nine flagellomeres). Four distinct types of sensory receptors were observed, including sensilla chaetica, sensilla trichodea, sensilla basiconica, and Böhm bristles. Three morphological subtypes of sensilla chaetica were found on the antennae, and sensilla trichodea were also categorized into three morphological subtypes. Sensilla basiconica was grouped into two morphological subtypes that were found on subsegments F2-F9 of the flagellum, and Böhm bristles were only found at the intersegmental joints between the scape and the head and between the scape and the pedicel. The antennae of male and female adults were similar in shape, length, and diameter. However, the length, diameter, distribution, and number of each of the four distinct types of sensilla on the males were significantly different from those on females. The types, lengths, diameters, numbers, and distributions of these sensilla were described, and their possible functions were also discussed. The results indicated that the base and end of an antennal segment have a similar sensillum density, but the middle section sensor density is significantly greater, especially for olfactory and gustatory sensilla, possibly because the joints are more involved in mechanical sensing. The density of sensors is closely related to its sensing function; so, future studies on the biology of olfaction and sexual communication in G. cantor will be facilitated by these observations.